The story of India [videorecording (DVD)] - Wood, Michael, 1948-; Jeffs, Jeremy (Maya Vision International : Distributed by PBS Home Video, 2008)
Historian Michael Wood chronicles the history of the Indian subcontinent, focusing especially on the diversity of its peoples, cultures and landscapes. The world's largest democracy and a rising economic giant, India is now as well known across the globe for its mastery of computer technology as it is for its many-armed gods and its famous spiritual traditions. But India is also the world's most ancient surviving civilization, with unbroken continuity back into prehistory. India's history is a ten thousand year epic but for over two millennia, India has been at the center of world history: birthplace of two world religions, home of an extraordinary spectrum of music, dance, literature, science, mathematics, economics, and a revolutionary idea whose power has yet to diminish. It has seen successive invasions from Alexander the Great and Genghis Khan to Tamburlaine and the British, all of whom left their mark but all of whom succumbed--in the end--to India herself.